Governmentality in Marine Spatial Utilization Policy: The Case of Riau Islands Province - Darmawan, Eki; Hapsa, Hapsa; Alfiandri, Alfiandri (Journal of Governance, 2024)
This study investigates the implementation of governmentality in policy utilization at sea, focusing on the case of the Province Riau Islands (Kepri). Governmentality, as a framework, Works theoretically proposed by Michel Foucault, applied in context policy utilization room sea for analysis of how the government of the province of Riau Islands manages and directs relations of interest and interaction with the environment of its unique sea. Using the qualitative method with the literature study, this study highlights various governmental aspects carried out by the government in the policy aspects of utilizing room sea in the Province of Kepri. Research results later will show that the government of the Province Riau Islands has prioritized governmentality for formulating policies that cover the sustainability of the ecosystem sea, participation of the community in the utilization of room sea, and integration of modern technology into the stages by showing the dominant actors who influence the political relations in the marine space utilization policy. This approach of collaboration between the government area, government center, and parties private sector at regional and international levels become characteristics important that will discussed in the implementation of governmentality in the Province of Kepri. In addition, recognizing the rights, customs, and wisdom of local public coasts has become an integral part of the utilization of the sea, creating a balance between the development economy and the conservation environment.